Pimpinellin Inhibits Collagen-induced Platelet Aggregation and Activation Through Inhibiting Granule Secretion and PI3K/Akt Pathway - Liu, Gang; Yuan, Zhaowei; Tian, Xiaoyun; Xiong, Xiuqin; Guo, Fang; Lin, Zihan; Qin, Zhen (Frontiers in Pharmacology, 2021)
Pimpinellin is a coumarin-like compound obtained from the root extracts of Toddalia asiatica Lam. However, whether pimpinellin can affect platelet function remains to be investigated. In the present study, pimpinellin pretreatment was found to effectively inhibit collagen-induced platelet aggregation in a dose-dependent manner, but does not inhibit platelet aggregation stimulated by thrombin or ADP. Moreover, pimpinellin-treated platelets showed reduced clot retraction and TxB2 production. In addition, pimpinellin also inhibited α granule（CD62P）and dense granule secretion (ATP release). Pimpinellin was also found to inhibit the adhesion and spreading of human platelets on fibrinogen-coated surfaces. Animal studies revealed no significant change in the tail bleeding time of mice in the pimpinellin group (40 mg/kg). Besides the blood parameters in mice was not affected, and pimpinellin (40 mg/kg) did not affect activated partial thromboplastin time(APTT) and prothrombin time(PT). Pimpinellin inhibited collagen-induced ex vivo platelet aggregation in mice. Immunoblotting studies showed that pimpinellin inhibited collagen-induced phosphorylation of PI3K-Akt-GSK3β and PKC/p38 MAPK in platelets. Treatment with LY294002 aggravated the inhibitory effect of pimpinellin on platelet aggregation and Akt phosphorylation. In conclusion, pimpinellin may be an effective drug for the prevention of platelet-related thromboembolic disease.